Differences in the estimation of the maximum oxygen consumption between 3 tests: Cooper test, The Multistage fitness test (shuttle run) and Polar fitness test (heart rate based) - Jovanovski, Jovan; Vuksanovikj, Vladimir; Jovanovski Ivan (Macedonian School Sports Federation, 2006)
On a sample of 11 respondents, students of the Faculty of Physics and Culture, Skopje, first year, three field tests were applied to assess the maximum oxygen consumption (Cooper test, multistage fitness test (Shutlle run) and Polar fitness test (Own Index) in order to compare the values obtained from the three applied tests. Different average values were achieved for the students in the three tests. The results of the Cooper test showed the greatest homogeneity compared to the others. It is recommended that the same test should be applied to the same subjects in the control measurements as at the beginning, because the tests applied in the research have different moving energy-productive and mental requirements for the subjects.
Разлики во прoценката на максималната кислородна потрошувачка со промена на куперовиот тест, повеќе скалестиот фитнес тест (multistage fitnes test-shutlle run) и поларовиот фитнес тест
Keywords: testing, students, endurance, anaerobic endurance, heart rate, Cooper test, multistage fitness test (Shuttle run), Polar fitness test (Own Index)